2011
DOI: 10.1163/016942410x508055
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Surface Properties of Silicone Elastomers to Improve Adhesion of Epoxy Topcoat

Abstract: Two modification routes have been applied to control the surface properties of spin-coated and screenprinted poly(dimethylsiloxane) (PDMS) layers and to improve their adhesion to a photopatternable epoxy resin topcoat. The first route is based on the optimization of low-pressure oxygen and ammonia plasma treatments to generate acidic or basic reactive surface groups capable of forming covalent bonds with the epoxy groups of the topcoat. The main disadvantage of these fast and practicable processes is the insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Electrokinetic measurements have been performed for several decades to study surface functionalities, modifications, and interactions of solids. Some recent examples from the authors' group include the characterization of polyelectrolytes, for example, for water purification by flocculation, 2 the proof of polymer surface activation by plasma treatment and polyelectrolyte adsorption to improve adhesion, 3 a study of the influence of fiber surface properties on fiber‐matrix interactions and mechanical properties of cementitious composites, 4,5 the monitoring of surfactant adsorption on photoresist to control capillary forces in photolithography, 6 and the investigation of functional and responsive thin polyelectrolyte layers on flat surfaces 7 and nanoparticles 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrokinetic measurements have been performed for several decades to study surface functionalities, modifications, and interactions of solids. Some recent examples from the authors' group include the characterization of polyelectrolytes, for example, for water purification by flocculation, 2 the proof of polymer surface activation by plasma treatment and polyelectrolyte adsorption to improve adhesion, 3 a study of the influence of fiber surface properties on fiber‐matrix interactions and mechanical properties of cementitious composites, 4,5 the monitoring of surfactant adsorption on photoresist to control capillary forces in photolithography, 6 and the investigation of functional and responsive thin polyelectrolyte layers on flat surfaces 7 and nanoparticles 8 …”
Section: Introductionmentioning
confidence: 99%
“…Electrokinetic measurements have been performed for several decades to study surface functionalities, modifications, and interactions of solids. Some recent examples from the authors' group include the characterization of polyelectrolytes, for example, for water purification by flocculation, 2 the proof of polymer surface activation by plasma treatment and polyelectrolyte adsorption to improve adhesion, 3 a study of the influence of fiber surface properties on fiber-matrix interactions and mechanical properties of cementitious composites, 4,5 the monitoring of surfactant adsorption on photoresist to control capillary forces in photolithography, 6 and the investigation of functional and responsive thin polyelectrolyte layers on flat surfaces 7 and nanoparticles. 8 Depending on size and shape of the investigated material, various techniques are available: electrophoresis NMR and particle charge detector for molecules and colloids, electrophoresis for diluted nanoparticle dispersions, electroacoustics for more concentrated dispersions, and streaming potential/streaming current measurements for fibers, powders, porous materials, and flat surfaces.…”
mentioning
confidence: 99%
“…Meanwhile, as for the foam part, the obvious signal at 922 cm À 1 belonged to the epoxy groups. The foam exhibited absorption bands due to N-H stretching and bending vibrations (ν N-H and δ N-H ) at 3387 cm À 1 and 1604 cm À 1 , respectively [14,15]. It was concluded that these N-H groups might be introduced from the amine curing agent in the cross-linking process.…”
Section: Ft-ir Resultsmentioning
confidence: 99%